Gambaran Pelaksanaan Senam Diabetes Mellitus di RSUP Dr.Sardjito Yogyakarta - Pramayanti, Fadillah; Aulawi, Khudazi; Pangastuti, Heny Suseani (School of Nursing Faculty of Medicine Universitas Gadjah Mada, 2008)
Please refer to the file